2012
DOI: 10.1007/s12603-012-0022-3
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition screening and early nutrition intervention in hospitalised patients in acute aged care: A randomised controlled trial

Abstract: Malnutrition in the older hospital population is common. Malnutrition screening on hospital admission facilitated targeted nutrition intervention, however length of stay and re-presentations were only reduced in older malnourished patients with an MNA score less than 17.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
91
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 39 publications
1
91
0
2
Order By: Relevance
“…Older patients are commonly malnourished during hospital stay (8) , and a high prevalence of malnutrition is found in hospitalized patients aged more than 65 years (13) . Therefore, the use of nutritional screening instruments (24) is critical given the prevalence of malnutrition and/or nutritional risk in hospitalized older adults (8,24) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older patients are commonly malnourished during hospital stay (8) , and a high prevalence of malnutrition is found in hospitalized patients aged more than 65 years (13) . Therefore, the use of nutritional screening instruments (24) is critical given the prevalence of malnutrition and/or nutritional risk in hospitalized older adults (8,24) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of nutritional screening instruments (24) is critical given the prevalence of malnutrition and/or nutritional risk in hospitalized older adults (8,24) . In a recent prospective study, Calvo et al, 2012, found that 77% of hospitalized older adults were at risk of malnutrition or malnourished according to the mini-nutritional assessment, and that low serum albumin, cholesterol, and vitamins A and D were associated with malnutrition or risk of malnutrition (3) .…”
Section: Introductionmentioning
confidence: 99%
“…In the subacute inpatient setting the prevalence is approximately 30-50% (6). Evidence suggests early recognition of malnutrition and initiation of effective nutrition support can alleviate negative outcomes associated with recovery from acute illness in the hospitalised elderly and reduce length of inpatient stay (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of difference between designated intervention and control areas may be attributed to the fact that this was at baseline and no intervention had taken place other than preparatory work. This helps to minimize possibility of confounding of the baseline differences on effect of intervention as shown in a study by Holyday et al(2012) 25 . Where significant differences at baseline exist appropriate analysis techniques will be used to control for them at follow-up and endline evaluation of the project.…”
Section: Source Of Nutrition Informationmentioning
confidence: 99%